Coenzyme A corrects pathological defects in human neurons of PANK2‐associated neurodegeneration. Issue 10 (11th August 2016) - Orellana, Daniel I; Santambrogio, Paolo; Rubio, Alicia; Yekhlef, Latefa; Cancellieri, Cinzia; Dusi, Sabrina; Giannelli, Serena G; Venco, Paola; Mazzara, Pietro G; Cozzi, Anna; Ferrari, Maurizio; Garavaglia, Barbara; et al.
Abstract: Pantothenate kinase‐associated neurodegeneration (PKAN) is an early onset and severely disabling neurodegenerative disease for which no therapy is available. PKAN is caused by mutations in PANK2, which encodes for the mitochondrial enzyme pantothenate kinase 2. Its function is to catalyze the first limiting step of Coenzyme A (CoA) biosynthesis. We generated induced pluripotent stem cells from PKAN patients and showed that their derived neurons exhibited premature death, increased ROS production, mitochondrial dysfunctions—including impairment of mitochondrial iron‐dependent biosynthesis—and major membrane excitability defects. CoA supplementation prevented neuronal death and ROS formation by restoring mitochondrial and neuronal functionality. Our findings provide direct evidence that PANK2 malfunctioning is responsible for abnormal phenotypes in human neuronal cells and indicate CoA treatment as a possible therapeutic intervention. Synopsis: Mutations in PANK2 cause PKAN disease. This belongs to a group of disorders characterized by progressive neurodegeneration and excessive iron deposition in the brain. PANK2 enzyme catalyzes the first step in CoA synthesis. iPSC‐derived neurons from PKAN patients display abnormal phenotypes. PKAN neurons show excitability defects and neuronal death. PKAN neurons present increased ROS levels and abnormal mitochondrial morphology and functions. PKAN neurons present cellular iron deficiency. PANK2 expression in patients' neurons reverts most of the abnormal phenotypes. CoA treatment restores the abnormal PKAN neuronal functions. Abstract : Mutations in PANK2 cause PKAN disease. This belongs to a group of disorders characterized by progressive neurodegeneration and excessive iron deposition in the brain. PANK2 enzyme catalyzes the first step in CoA synthesis. iPSC‐derived neurons from PKAN patients display abnormal phenotypes.